2019
DOI: 10.1002/ajoc.201900055
|View full text |Cite
|
Sign up to set email alerts
|

Tris(Pentafluorophenyl)Borane‐Driven Stereoselective O‐Glycosylation with Glycal Donors under Mild Condition

Abstract: Activation of glycal donors was achieved using tris (pentafluorophenyl)borane [B(C 6 F 5 ) 3 ] under mild reaction conditions. The glycosylation reaction proceeded efficiently with a wide range of sugar and non-sugar acceptors and provided α-selective glycosides in high yield. Interestingly, under different reaction conditions, Ferrier rearrangement products or 2-deoxyglycosides (i. e. addition products) were obtained as major products with benzyl-protected glycal donors.[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ferrier rearrangement is an allylic rearrangement of glycals . Classically, Ferrier rearrangement has been promoted by acid catalysts to form various glycosyl bonds, such as C–O, C–C, and C–S bonds (Scheme a), and chemical oxidants have also been reported as promoters (Scheme b). Most recently, Nagaki and coauthors reported that a flash electrochemical approach afforded efficient conversion using short-lived intermediates (Scheme c) .…”
Section: Introductionmentioning
confidence: 99%
“…Ferrier rearrangement is an allylic rearrangement of glycals . Classically, Ferrier rearrangement has been promoted by acid catalysts to form various glycosyl bonds, such as C–O, C–C, and C–S bonds (Scheme a), and chemical oxidants have also been reported as promoters (Scheme b). Most recently, Nagaki and coauthors reported that a flash electrochemical approach afforded efficient conversion using short-lived intermediates (Scheme c) .…”
Section: Introductionmentioning
confidence: 99%